HUBUNGAN POLA MAKAN DAN STRES DENGAN KEJADIAN GASTRITIS PADA SISWA SMPN 14 KELURAHAN BAROS KOTA SUKABUMI - Amelia Permana Putri, Della; Hadiyanto, Hendri; Tarwati, Kartika (Lafadz Jaya Publisher, 2023)
Adolescents are susceptible to various diseases, one of which is gastritis. Gastritis occurs in people who have a bad diet that can stimulate stomach acid production and one of the factors that can cause gastritis symptoms is stress which can increase HCL in the stomach. The purpose of this study was to identify the relationship between diet and stress with the incidence of gastritis in students of SMPN 14 Baros Village, Sukabumi City. This research method is quantitative research with a correlation descriptive design using a cross sectional approach. The number of respondents in this study was 51 respondents. The sampling technique in this study was simple random sampling. The statistical test of this research is the Chi Square Test. The results showed that the incidence of gastritis reached 38 respondents (74.5%), 27 respondents (52.9%) had a bad diet, in the stress category most respondents experienced moderate stress with 17 respondents (34.0%). From the chi square test for cross-tabulation of eating patterns with the incidence of gastritis, the result is p-value = 0.000 < ɑ = 0.05, then H₀ is rejected and Ha is accepted which means that there is a relationship between pattern and the incidence of gastritis with a contingent coefficient value of 0.621 which is categorized as strong. For cross-tabulation of stress and gastritis with p-value = 0.004 < ɑ = 0.05, H₀ is rejected and Ha is accepted, meaning that there is a relationship between stress and gastritis with a contingent coefficient value of 0.460 which is categorized as moderate or sufficient. In this study there is a relationship between diet and the incidence of gastritis at SMPN 14 Baros Village, Sukabumi City.